Myth and Authority : Giambattista Vico's Early Modern Critique of Aristocratic Sovereignty. - Bertland, Alexander U. (SUNY Series in Contemporary Italian Philosophy Ser., 2022)
Argues that Giambattista Vico's early modern account of Roman mythology was a sophisticated attempt to present an epistemological and political critique of the aristocratic way of conceiving the world.